Contribution of Electrolysis within an Integrated System for a Poultry Slaughterhouse Wastewater Treatment - Kulyash Meiramkulova (MDPI AG, 2021)
Treatment of poultry slaughterhouse wastewater before disposal or reuse is an essential part of human health and environmental protection in general. This study aimed to investigate the influence of the pre-treatment system based on electrolysis technology within an integrated lab-scale treatment plant in the removal of contaminants from poultry slaughterhouse wastewater. Several treatment units (averaging tank, feather catcher, fat catcher, and coarse mechanical filter) were connected in series before the electrolysis chamber. While in general, the entire integrated system also included some other units such as ultra-filtration, reverse osmosis, and the ultraviolet lamp connected in series. From the analysis results, it was observed that the pre-treatment phase with electrolysis had a significant influence on the general performance of the treatment plant. The pre-treatment contributed to about 33.5% to 100% in the general contaminants’ removal efficiency. The highest contribution was observed from the total chlorine (100%), nitrate (98.2%), as well as BOD (95.3%). The lowest contribution was observed from the nitrite removal, with 33.5%. This study revealed further that the integration of electrolysis technology in a wastewater treatment system has a significant potential for developing an effective wastewater treatment plant.